Peran BUMDES Dalam Pengembangan Objek Wisata Pantai Di Desa Pitu Kecamatan Tobelo Tengah Kabupaten Halmahera Utara - Tambajong, Junisa Eflian; Tambas, Jane Sulinda; Timban, Jean Fanny Junita (Sam Ratulangi University, 2023)
The purpose of this study was to determine the role of Bumdes on community Awareness, Capacity and Empowerment in the Development of the Coastal Tourism Village of Pitu Beach in Tobelo Tengah District. Qualitative data analysis method to determine the role of community empowerment at the stages of Awareness, Capacity, and Empowerment. The data analysis method used in this research is descriptive analysis and then interpreted to draw conclusions. Based on the results of research on the role of Bumdes on Awareness, Capacity and Empowerment of the community in the Development of the Coastal Tourism Village of Pitu Beach in Tobelo Tengah District, it can be concluded; Awareness aspect, behavior change from unwilling to willing, namely increasing awareness of the Village community in maintaining the cleanliness and security of the village settlement environment and tourist sites; Aspects of capacity, increasing the skills of community business actors in managing businesses at the Pitu Beach Tourism location, such as how to make food and drinks typical of Pitu village; Aspects of Empowerment, increasing business turnover managed by the community at the Pitu beach tourist location. Because of the trust of the village government through Bumdes, the Village Government provides grant funds from village funds for business capital.